Answer:
the inverse of a function is the exact opposite
Step-by-step explanation:
For this, we will be using the quadratic formula, which is
, with a=x^2 coefficient, b=x coefficient, and c = constant. Our equation will look like this: ![x=\frac{-6+/-\sqrt{6^2-4*(-2)*3}}{2*(-2)}](https://tex.z-dn.net/?f=%20x%3D%5Cfrac%7B-6%2B%2F-%5Csqrt%7B6%5E2-4%2A%28-2%29%2A3%7D%7D%7B2%2A%28-2%29%7D%20)
Firstly, solve the multiplications and the exponents: ![x=\frac{-6+/-\sqrt{36+24}}{-4}](https://tex.z-dn.net/?f=%20x%3D%5Cfrac%7B-6%2B%2F-%5Csqrt%7B36%2B24%7D%7D%7B-4%7D%20)
Next, do the addition: ![x=\frac{-6+/-\sqrt{60}}{-4}](https://tex.z-dn.net/?f=%20x%3D%5Cfrac%7B-6%2B%2F-%5Csqrt%7B60%7D%7D%7B-4%7D%20)
Next, your equation will be split into two:
. Solve them separately, and your answer will be
Answer:
f^-1(v)=v/x-3/x
Step-by-step explanation:
Answer: i think the answer is -3
Step-by-step explanation: